Ojibwe - Lajiness, Katie (2019)
This title introduces readers to the Ojibwe people and covers traditional ways of life, including social structure, homes, food, art, clothing, and more. Also discussed is contact with Europeans and American settlers, as well as how the people keep their culture alive today.
Amazing people -- Ojibwe territory -- Home life -- What they ate -- Daily life -- Made by hand -- Spirit life -- Storytellers -- Fighting for land -- Back in time -- The Ojibwe today.
Includes index.
Ages 7-10
Keywords: Ojibwa Indians -- Juvenile literature; Ojibwa Indians; Juvenile works